Preliminary Studies on Seed Germination Behaviour Berberis lycium, Royle-an Important Shrub for Reclamation of Wastelands in the Himalaya - Bahuguna, V. K.; Rawat, M. M. S.; Joshi, S. R. (Indian Forester, 1988)
This paper presents the results of experiments carried out in order to determine seed morphology and germination behaviour of Berberis lycium Royle.